Molecular typing of Brucella species by PCR-RFLP and SSCP - HEMADE, M V; GANDGE, R S (The Indian Journal of Animal Sciences, 2016)
PCR-RFLP and PCR-SSCP help to understand variabilities in Brucella spp. genome which in turn assist in planning epidemiological strategies for control of brucellosis in animal population and thereby human transmission. Restriction fragment length polymorphism (RFLP) analysis was carried out for BCSP31 (223 bp) gene of 15 isolates using restriction enzyme HaeII and BsaBI. All isolates yielded a similar restriction pattern as that of reference strains i.e. 189 + 34 bp and 164 + 60 bp fragments with HaeII and BsaBI restriction enzyme, respectively. PCR- SSCP analysis of BCSP 31 gene of 33 Brucella spp. isolates was carried out. Seven different SSCP band patterns designated from “A” to “F” were observed. Out of 33 isolates of Brucella spp., 19 isolates showed SSCP profile similar to ATCC reference strains of Brucella spp. designated as band pattern “A” indicating no polymorphism. Whereas, 14 isolates showed polymorphism in SSCP band pattern designated from “B” to “G”. Band pattern “A” was the most common in 19 (57.58 %) isolates followed by “B” in 6 (18.18 %) isolates and “G” in 4 (12.12 %) isolates, whereas “C”,”D”,”E”, and “F” band patterns were found in each of 1 (3.03 %) isolate. SSCP band pattern “A” was observed most commonly in buffalo (10) followed by human (6) and cattle (3). The SSCP band pattern “B” was found in equal proportion in cattle and buffalo (3 each). The “C” and “E” SSCP band patterns were observed in cattle, whereas “D” and “F” SSCP band pattern was noticed in buffalo and human isolates, respectively. The “G” SSCP band pattern was observed in 3 cattle and 1 goat isolate. In cattle-ABCEG, buffalo-ABD, goat-G and in human-AF band patterns were seen. Comparative results of RFLP and SSCP in 15 isolates showed that, PCR-SSCP is more sensitive than RFLP for detection of polymorphism in BCSP31 gene.